(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To analyze some factors related to treatment adherence among outpatients with type 2 diabetes and diabetic nephropathy at Thanh Nhan Hospital in 2025. Subjects and Methods: A cross-sectional descriptive study with analytical components was conducted on 104 outpatients diagnosed with type 2 diabetes and diabetic nephropathy. Results: Patients aged 60 or younger, without health insurance, lacking support, having a disease duration of less than 5 years, and having insufficient disease knowledge were more likely to have poor treatment adherence. Conclusion: There were statistically significant associations between treatment adherence and factors such as age, health insurance status, social support, disease duration, and disease-related knowledge.